Horses That Weep, Birds That Tell Fortunes: Animals in South Asian Muslim Ritual and Myth - Pinault, David (Religions of South Asia, 2013)
This article discusses whether South Asian Muslims view non-human animals as more than utilitarian markers and metaphors for human desires, or instead regard animals not as objects to be exploited but as autonomous beings who have their own intrinsic worth. Two cases will be examined. The first study explores the annual Shia Zuljenah or ‘Horse of Karbala’ procession in Ladakh (India) and Lahore, when a riderless horse is caparisoned to represent Zuljenah (the stallion ridden by Imam Husain ibn ‘Ali into combat at Karbala) and is then led through the streets as the focus of a procession involving communal selfflagellation, outbursts of wailing and agitated attempts by thronging participants to press against the horse so as to capture Husain’s blessing. This is particularly significant as medieval sources and contemporary informants claim Zuljenah wept and beat its head against the ground empathetically at the death of its master, thus showing devotion and grief. Second, animal-transformation tales will be explored as a way of considering links between Hinduism and Islam in human understandings of animals. Controversies about Hindu influence overshadow rituals involving animals in South Asian Muslim devotionalism today, as exemplified in the use of fortune-telling parrots in Lahore and Rawalpindi. Certain Pakistani Sufis and sorcerers claim mastery over jinns that take the shape of gecko lizards to spy out malevolent spirit-world presences, including ‘Hindu jinns’ that are believed to infest various localities in Lahore.